Rede social virtual de professores especializados e a escolarização de estudantes com deficiência intelectual - Milanesi, Josiane Beltrame (2017)
The Brazilian educational policy states that schooling of the Target Public of the Special Education (PAEE, in portuguese) should be performed at ordinary classrooms from regular schools, associated to the Specialized Educational Attendance (AEE, in portuguese) performed complementarily or supplementarily to the schooling in common classes. However, the AEE guidelines are still not clear, mainly in the case of students with intellectual disabilities, who constitutes the majority of the PAEE in the country. Due to difficulties, doubts and concerns faced by AEE teachers as their students fall into the intellectual disabilities category, this study aims to connect these teachers in a virtual network on the internet, so that they help to unravel how AEE has been applied for their students. Besides of knowing how different teachers of multifunctional resource room (SRM, in portuguese) dealt with their students with intellectual disabilities, it was questioned if they were able to demonstrate that the experience was formative, when they had the opportunity to make exchanges about their own teaching work, in the sense of expanding their knowledge about the teaching of these students and of bringing elements to suggest proposals for the AEE. Based on this reality, this study aims to describe and analyze the pedagogical practice in AEE for students with intellectual disabilities and to investigate strategies to provide training for teachers of these students. This study built an social network on the internet with twelve AEE teachers of students with intellectual disabilities who participated in activities of ten real teaching cases, and such cases were elaborated by the participants. The data were collected from records obtained from tools available in the virtual environment, based on the responses of the participant teachers about the formulated questions for each of the teaching cases and on the comments of the participants after reading the devolutives of the synthesis documents of the 10 cases. The teachers productions and the exchanges among them were recorded in the virtual environment and were analyzed using the Grounded Theory method and its analysis techniques, in order to produce a conceptual ordering of the data, with the support of ATLAS/ti. The data analysis suggests that the SRM might be potentialized if real possibilities of acting, training and joint work among the professionals that work with students with intellectual disabilities were given, with possibility to result in significant proposals to provide progress of the teaching and learning of these students. However, it is necessary to invest in more studies focusing on didactic-pedagogical actions of the AEE professionals, so that more effective guidelines can be developed to improve the quality of the education of students with intellectual disabilities.